Loyal Customer Classification Using Fuzzy Logic Inference System - Rosena Shintabella; Imma Ismaniar; Muhammad Fikry Januar; Zulfikar Fauzi (Politeknik Mardira Indonesia, 2024)
A company will be better if it can maintain its existence in the community, then the company is more oriented to acquire new customers.But one day it will lose customers if it is not managed properly. In this case there is a customer satisfaction variable that affects customer loyalty in a company. In this study apply fuzzy logic inference method to select customers with the highest level of loyalty. The extraordinary value of a customer towards a company certainly cannot be declared with certainty or exactness. So that the decision making is very suitable when using the concept of fuzzy logic, because it can represent variables that are vague or not exact. The case study in this study was conducted in a trading company or supermarket. The result of its implementation is that the system can determine who is the most loyal of several selected samples of customers.